ANALISIS SWOT PADA STRATEGI PEMASARAN USAHA JAMUR TIRAM DUA PUTRA DI KECAMATAN SINJAI BARAT - Nurhaliza, Nurhaliza; Astaman, Putra; Megawati, Megawati; Nurdin, Fadilah (Jurnal Riset Multidisiplin Agrisosco, 2025)
The marketing strategy of Dua Putra oyster mushroom business still faces obstacles in marketing its oyster mushroom products, as farmers only sell them to traders and consumers who are still local communities. This study aims to analyze the marketing strategy of the Two Sons Oyster Mushroom Business in Gunung Perak Village, West Sinjai District, Sinjai Regency, using a SWOT analysis approach. This study uses a quantitative descriptive method with data collection techniques through observation, interviews, distribution of questionnaires to 5 respondents, and documentation. The results of the study indicate that the internal factors that are strengths in the Dua Putra oyster mushroom business are that the oyster mushroom products are of good quality and able to compete in the local market, while the main weaknesses of the Dua Putra oyster mushroom business are that the mushroom products spoil quickly and the production facilities are still simple. External factors show that the biggest opportunity for the Dua Putra oyster mushroom business is that oyster mushrooms can be processed into derivative products, so that they do not only sell raw oyster mushrooms, but they still need to be aware of business threats such as the difficulty of obtaining raw materials. The results of the IFAS and EFAS calculations show that the scores are 1.958 and 0.628, respectively, placing the Dua Pura Oyster Mushroom Business in Quadrant I of the SWOT matrix, meaning it is in an aggressive strategy position.